We have the following equation:
2 (x-3) ^ 2 + 10 = 82
We must clear x.
We pass the constant terms to one side of the equation:
2 (x-3) ^ 2 = 82 - 10
2 (x-3) ^ 2 = 72
(x-3) ^ 2 = 72/2
(x-3) ^ 2 = 36
Square root to both members:
x-3 = +/- root (36)
x-3 = +/- 6
The solutions are:
x1 = 6 + 3 = 9
x2 = -6 + 3 = -3
Answer:
x1 = 9
x2 = -3
Answer:
я не знаю потому что я не говорю по русски
Step-by-step explanation:
Answer:
0.57
Step-by-step explanation:
a 2 pint jug costs $2.28
2 pints=4 cups
$2.28/4=0.57
Answer:
SAS,
Step-by-step explanation:
2 sides and the included angle.
Answer:
The answer is .24, or 6/24
Step-by-step explanation:
Its easiest to convert the 2 answers into decimals and then solve.